THE ROLE OF TECHNOLOGY IN TEACHING INSTRUMENTAL PHONETICS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Instrumental phonetics involves the use of technology to analyze and measure the physical properties of speech sounds, including articulation, acoustics, and auditory perception. With advancements in technology, teaching phonetics has evolved from traditional methods to more interactive and engaging techniques that leverage digital tools. These tools enable learners to analyze speech in real-time, visualizing sound waves, formants, and articulatory movements, making abstract concepts more concrete and easier to understand. This paper investigates the role of these technologies in phonetics education, analyzing how they enhance the learning experience and the challenges they introduce.